Results of the Expert Forum on the application of perampanel in routine clinical practice - article Editorial (Эпилепсия и пароксизмальные состояния)
In February 2020, in Moscow, Expert Forum was held on the issues of the application of perampanel in routine clinical practice. The main aim of the Forum was to discuss the tolerance and safety profile of perampanel in patients with epilepsy in different age and gender groups in the conditions of routine clinical practice. Leading experts in neurology and epileptology took part in the Forum, wherein the acute data on the efficiency and safety of perampanel and the management of potential risks were presented.